Pruritus - ein weiter Weg von der Neurophysiologie zur Klinik - Schmelz, Martin (Der Hautarzt, 2020)
Background The mutual exchange of results between basic sciences and clinical research as well as their translation into practice, also with regard to chronic pruritus, is currently to be seen as an ambition or hope rather than established practice. Objective In view of the rapid developments in the field of neurophysiological basics of pruritus, the aim is to clarify how these new concepts can be brought in line with clinical understanding. Materials and methods A review is provided. Results After the peripheral and spinal processing pathways for pruritus in the mouse were characterized with molecular markers, we are currently working on the translation of this information to the only functionally defined nerve fiber classes in humans. However, it is still unclear whether these processing pathways are crucial for the explanation of chronic pruritus in patients, since inflammation or neuropathy can significantly alter nerve populations and neuronal networks. Therefore, molecular target structures, which have emerged from results of basic research, need to be verified in patients. The gold standard, however, remains the patient with clinical observation and testing. Specific stimulation methods from neurophysiology can help to test hypotheses from basic research directly on patients, while also providing impulses for further development of research concepts. Conclusions Translation in medical research is now perceived by many researchers as a hackneyed buzzword. In the field of pruritus research, however, the exchange of results and concepts based on the mutual appreciation of expertise appears attractive, highly relevant, and promising.